Pelatihan Public speaking dalam Penguatan Kemampuan Public Speaking Santri Assunniyyah Kencong - Fadholi, Amak; Al Karim, Ubaidillah Ali; Arief, M. Insar (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
The importance of good public speaking skills for santri is one of the important assets where santri in the development of their da'wah, public speaking skills can be an effective tool in conveying various information, fostering motivation, persuasive approaches or just as a discussion. in this increasingly competitive era, santri in addition to mastering religious knowledge must also have good communication skills in public. Of course, it is not easy for someone to be good and expert in public speaking, it is necessary to learn and practice and dare to try activities related to public speaking. Seeing the results of the observations that have been made, the ability of public speaking in Assunniyyah Islamic Boarding School is still not optimal, this is the basis for us to carry out public speaking assistance for Assunniyyah students in order to improve their ability and confidence in public. The mentoring method used is Empowerment-Based Research (EBR), which focuses on the active involvement of the supported community in the planning, implementation and evaluation of the programme. While the training method used is the drill method, which emphasises repetition in activities or practice with what has been learned by each student. The results of this service are increased self-confidence and broader public speaking skills of the students. This increases the value of the students